Two new Triassic sphinctozoan sponge species from near Kantang, Trang Province, Southern Thailand - Senowbari-Daryan, Baba; Ridd, M. F. (Palaeontologische Zeitschrift, 2008)
A black limestone collected from near Kantan, Trang Province, southern Thailand, contains two species of sphinctozoan sponge which have been namedAmblysiphonella parva n. sp. andPlatythalamiella minima n. sp. The former is a cylindrical chambered sponge with an axial spongocoel and ring chambers.P. minima is an asiphonate and tabular sponge characterized by small chambers arranged in one or two layers above and beside each other. Both are the smallest known species in their respective genera. Hypercalcified sponges have not previously been reported from the Triassic of Thailand.
UnivIS-Import:2017-11-07:Pub.2008.nat.dgeo.IGM.LP.amblys
Keywords: Sponges; Amblysiphonella; Platythalamiella; Triassic; Thailand